Comparative effects of vonoprazan-based and esomeprazole-based dual therapy on Helicobacter pylori eradication and short-term gut microbiota changes - Yi Liu; Xuetian Qian; Jiayue Yao; Chunming Fei; Zhenyu Zhang; Zongdan Jiang (Gut Pathogens, 2026)
Abstract Objective This study aimed to compare the Helicobacter pylori (H. pylori) eradication efficacy, safety, patient compliance, and short-term effects on the gut microbiota of vonoprazan-based potassium-competitive acid blocker (P-CAB) dual therapy and esomeprazole-based proton pump inhibitor (PPI) dual therapy. Methods A total of 110 H. pylori-positive patients were enrolled and non-randomly assigned to the P-CAB group ( n = 50, vonoprazan 20 mg bid + amoxicillin 750 mg qid) or the PPI group ( n = 60, esomeprazole 20 mg qid + amoxicillin 750 mg qid). Twenty-two H. pylori-negative individuals served as healthy controls (HC). Eradication was assessed by the ¹³C-urea breath test four weeks after treatment. Fecal samples were collected at baseline (week 0), after eradication (week 2), and at confirmation (week 6) for 16 S rRNA gene sequencing to analyze gut microbiota diversity, composition, and functional changes. Results The P-CAB group showed a higher eradication rate than the PPI group across all analysis sets, reaching statistical significance only in the per-protocol analysis (97.73% vs. 84.20%, P = 0.04). Adverse reactions and patient compliance did not differ between the two groups ( P > 0.05). Both regimens altered the diversity, composition, and functional pathways of the gut microbiota, with gradual recovery over time. Initial declines in microbial diversity were more pronounced in the P-CAB group, while functional pathway recovery tended to be faster. Both groups showed an increase in potential pathogenic bacteria and a decrease in short-chain fatty acid-producing bacteria after treatment. Conclusions VA dual therapy achieved a higher H. pylori eradication rate than EA dual therapy in all analysis sets, but statistical significance was reached only in the per-protocol analysis. Safety and patient compliance were comparable between the two regimens. Both treatments transiently disrupted the diversity, composition, and function of the gut microbiota, with gradual recovery over time.